DEIKSIS DALAM KUMPULAN CERPEN PILIHAN KOMPAS 2014 - Sholihah, Ni’matus (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
The purpose of the study was to describe from of deixis. (1) persona deixis(2) place deixis and (3) time deixis in the short stories compas sellection 2014. Concluded that the ten short stories that exist on the short stories compas selection in 2014, has the persona deixis, place deixis, and deixis time. Deixis persona in ten short stories is the must dominant single deixis persona and a single therd. deixis found place is the library and grave (Passiliran, Toraja Language), Tarra, uterus tree, street names, danstore name. While deixis time enccuntered such word for months, a week ago, when, and meaningful time atmosphere. Deixis existing therd in the short story is a short story of the intrinsic factor that is setting the place, time, and characterization.